Age-specific risk of substance use disorders associated with controlled medication use and misuse subtypes in the United States. (March 2019) - McCabe, Sean Esteban; Wilens, Timothy E.; Boyd, Carol J.; Chua, Kao-Ping; Voepel-Lewis, Terri; Schepis, Ty S.
Abstract: Objective: To examine the age-specific risk of past-year substance use disorders (SUDs) associated with use and misuse of prescription opioids, stimulants, sedatives and tranquilizers. Methods: The authors analyzed nationally representative data from 114, 043 U.S. individuals aged 12 and older in the 2015–2016 National Survey on Drug Use and Health. For each controlled medication class, logistic regression was used to model any past-year SUD as a function of use pattern: no use or misuse, use without misuse, prescription drug misuse (PDM). Among individuals reporting PDM, logistic regression was used to model any past-year SUD as a function of PDM subtype (misuse of someone else's medication only, misuse of one's own medication only, and misuse of one's own and someone else's medication). Analyses were stratified by age group. Results: Controlled medication use was associated with higher odds of any past-year SUD compared to no use in many age groups and medication classes. Compared to non-use, PDM was associated with higher odds of any past-year SUD across virtually all age groups and medication classes. Compared to misuse of one's own medication only, misuse of both someone else's and one's own medication was associated with higher odds of any past-year SUD for many age groups and medication classes among individuals reporting PDM. Conclusions: Clinicians should screen all controlled medication users for PDM and SUDs. Age-specific screening may be required due to heterogeneity in the prevalence and risks of use and misuse of different medications. Determination of PDM subtype can guide interventions to prevent SUDs. Highlights: Medication use was associated with higher risk of SUD but varied by age and drug class. Prescription drug misuse was associated with the highest risk of SUD for all ages. Nearly one in two young adults engaged in prescription drug misuse had a SUD. Misuse of one's own and someone else's medication had highest risk of SUD. Close medication monitoring and age-specific SUD screening tools are needed.